Genome-wide RNA-Sequencing analysis identifies a distinct fibrosis gene signature in the conjunctiva after glaucoma surgery - Cynthia Yu-Wai-Man (Nature Portfolio, 2017)
Abstract Fibrosis-related events play a part in most blinding diseases worldwide. However, little is known about the mechanisms driving this complex multifactorial disease. Here we have carried out the first genome-wide RNA-Sequencing study in human conjunctival fibrosis. We isolated 10 primary fibrotic and 7 non-fibrotic conjunctival fibroblast cell lines from patients with and without previous glaucoma surgery, respectively. The patients were matched for ethnicity and age. We identified 246 genes that were differentially expressed by over two-fold and p < 0.05, of which 46 genes were upregulated and 200 genes were downregulated in the fibrotic cell lines compared to the non-fibrotic cell lines. We also carried out detailed gene ontology, KEGG, disease association, pathway commons, WikiPathways and protein network analyses, and identified distinct pathways linked to smooth muscle contraction, inflammatory cytokines, immune mediators, extracellular matrix proteins and oncogene expression. We further validated 11 genes that were highly upregulated or downregulated using real-time quantitative PCR and found a strong correlation between the RNA-Seq and qPCR results. Our study demonstrates that there is a distinct fibrosis gene signature in the conjunctiva after glaucoma surgery and provides new insights into the mechanistic pathways driving the complex fibrotic process in the eye and other tissues.